Control interno de las cuentas por cobrar en la Empresa Agenmil - La Moneda agencia de viajes s.a. en la ciudad de Guayaquil del periodo 2020 – 2021. - Torres Cabezas, Kristel Melina (2023)
The internal control of accounts receivable in an organization is essential to be able to carry out a correct management of the management policies, both of the credit portfolio, and of the collection process, which depends on the priority given to each one of the credit policies that the entity has. This case study has the theme of "Internal Control of accounts receivable in the company AGENMIL - LA MONEDA AGENCIA DE VIAJES S.A. in the city of Guayaquil for the period 2020 - 2021 "has the main objective of analyzing the internal control of accounts receivable of the aforementioned company, using information collection instruments such as the internal control questionnaire, analysis of accounts receivable and uncollectible accounts of two periods and observation, using documentary and field research methods with a qualitative approach in order to provide the most information to support this case study.